DPD RI Antara Realitas dan Idealitas - Khoirotin Nisa (Kopertais Wilayah X Jawa Tengah, 2017)
AbstractThe Eksistences of DPD RI has risen society’s hope ini the region that the regional interest and the problems which are faced by the region can be risen and fought to the national level. DPD RI guarantee the regional interest will be equal with the national interest. But with the limited authority, DPD cannot do duty optimally. DPD as a new institution still fight to improve its authority to optimize its role as regional representation.Keyword : DPD RI, regional representation, society’s hope